PERANAN SEQUENCE SWI (SUSCEPTIBILITY WEIGHTED IMAGING) PADA PEMERIKSAAN MRI BRAIN KLINIS PARKINSON - Eva Maulidiana Hikmah; I Putu Eka Juliantara; Nadra (Pusat riset dan Inovasi Nasional, 2023)
The Role of SWI (Susceptibility Weighted Imaging) Sequence in Clinical Parkinson’s MRI Brain Imaging. Magnetic Resonance Imaging (MRI) is a technique for imaging body crossings based on the principle of magnetic resonance of hydrogen atoms. Brain MRI examination aims to see anatomy and abnormalities within the brain to establish clinical diagnosis, pathological abnormalities, tumors, and surrounding abnormalities. Imaging examinations are also conducted to find other causes of Parkinsonism. Head MRI is one of the non-invasive examinations performed to help confirm the diagnosis of Parkinson's disease. This study aims to determine the procedure for Brain MRI examination with Parkinson's clinical and to determine the sequence information SWI (Susceptibility Weighted Imaging) can establish clinical diagnosis of Parkinson's. This study is qualitative descriptive with a case study approach. The subject consists of three patients with clinical Parkinson's. All subjects performed MRI brain 3 tesla examinations to determine the procedure and sequence information used. The research results were obtained according to the theory using an additional 2 mm sequence, while in the field using 0.9 mm sequence the examination was conducted using the head coil of the patient's position, namely supine, head first. Sequences used in field inspections are AAHead Scout, t1 fl2d transversal, t2 tse (time spin echo) dark fluid transversal, t2 tse (time spin echo) transversal, ep2d diff (diffusion) 4scan trace, asl 3d transversal, tof cs carotids, flow pc3d MRV (magnetic resonance venography), tof brain MRA (magnetic resonance angiography), t2 swi (susceptibility weighted imaging) 3d transversal 0.9 mm. The thin axial sequence of 0.9 mm is more likely to see Parkinson's anatomical abnormalities, higher SNR and better spatial resolution than using a 2 mm slice thickness.